The relationship between training load and perceived sleep quality and quantity in professional rugby sevens players during an international competitive season - Opperman, S. (University of Stellenbosch, 2020)
Sleep is an essential component in the performance of athletes. Exercise performed during the day might influence subsequent sleep and disrupt the quality and quantity (duration) thereof. How an athlete perceived the quality and quantity of sleep is important in monitoring their well-being. By knowing the effects of exercise on subsequent sleep as well as how sleep is affected during a competitive season, should assist coaches in the planning and scheduling of training sessions to allow adequate recovery for athletes. Athletes should also be educated on the value of good quality and quantity of sleep to enhance their performance. The primary aim of this study was to determine if there is a relationship between variation in daily training load (dTL) and the subsequent night`s perceived sleep quality (pSQ) and perceived sleep quantity as perceived sleep duration (pSD) of Rugby Sevens players. The secondary aim of this study was to determine if there is a relationship between pSQ and pSD in Rugby Sevens players as it was hypothesised by the researcher that there is a relationship between better sleep quality and longer sleep duration perceived by players. The third aim of this study was to determine if there was a change in training load during the 31-week season while the fourth aims were to determine if there was a change for pSQ and pSD for the same 31-week period. During an international, 16 elite professional Rugby Sevens players from the South African National Rugby Sevens squad were observed for 31 weeks during a competitive season. Training load consists of two components: intensity, measured as the rate of perceived exertion (RPE) and the duration of the exercise sessions which was termed session training load (sTL) for the purpose of this study. For multiple training sessions or matches on a day, all sTL for the day were summed in order to provide the daily training load (dTL). This was measured for all training sessions, captain`s runs and matches. Each player`s dTL was correlated with pSQ and pSD for the subsequent night`s sleep. The duration of training sessions or matches were also summed to provide the total training or match time for the day called the daily duration (dD). The highest intensity the player was exposed to for any of the exercise sessions on the day was termed the maximum RPE (mRPE) by using the highest RPE score provided for any of the sessions, should there have been more than one training session on a day or more than one match. For training sessions, captain`s runs and matches mRPE and the dD were also correlated with the subsequent night`s pSQ and pSD. Self-reported perceived sleep scores have been shown to be reliable in a team set-up. After training sessions pSD were negatively impacted by the daily duration (DD) (r = -0.16) (p < 0.01), the intensity (mRPE) (-0.12) (p < 0.01) and the daily training load (dTL) (-0.17) (p < 0.01) of the training session. After matches pSQ was negatively impacted by the DD (r = -0.4) (p < 0.01) and dTL (-0.37) (p < 0.01) of the playing time in the matches. Neither pSQ nor pSD was significantly affected after captain`s runs (p > 0.05). Furthermore, it seems that sleep quality and duration are coupled as A moderate positive correlation (r = 0.32, p < 0.01) was found between pSQ and pSD during the season. There was a significant difference in pSQ for each additional hour of pSD from more than five hours of sleep to more than eight hours of sleep (p > 0.05). These findings indicated that there might be a relationship between sleep duration and training load, intensity and the duration of training sessions after training sessions. Sleep quality might have a relationship with the training load and duration of playing time in matches. Also, sleep quality and sleep duration seem to have a positive relationship with each other. Lastly, no significant changes (p > 0.05) could be found between the start of the season and the end of the season for training load, pSQ and pSD. Notwithstanding the results of this study that showed exercise might have an impact on subsequent sleep quality and quantity, other circumstances could also contribute to the findings. Body soreness, early morning training session and circadian desynchronization, for instance, are possible confounding variables which may hinder sleep quality and quantity of elite athletes. Acquiring a better understanding of how exercise and sleep influence each other can assist in planning to optimise performance. In the current study, only the effects of exercise on sleep were assessed. It might be relevant to examine the effects of the previous night`s sleep on subsequent training in future studies. In conclusion, findings from this study indicate the need for elite athletes to increase sleep duration in order to enhance sleep quality which is closely coupled with performance benefits.